Inversion of traditional gender roles and intimate partner violence against pregnant women - Marizélia Rodrigues Costa Ribeiro; Antônio Augusto Moura da Silva; Lilia Blima Schraiber; Joseph Murray; Maria Teresa Seabra Soares de Britto e Alves; Rosângela Fernardes Lucena Batista; Livia dos Santos Rodrigues; Heloisa Bettiol; Ricardo de Carvalho Cavalli; Marco Antonio Barbieri
This study analyzed the association between the inversion of traditional gender roles and exclusive psychological and physical/sexual intimate partner violence, in a cross-sectional study of Brazilian pregnant women, identified through prenatal services in the municipalities of São Luís, Maranhão State (n = 992) and Ribeirão Preto, São Paulo State (n = 943). The pregnant women ranged from 12 to 45 years. Inversion of traditional gender roles was assessed by calculating differences in age, education and occupation between pregnant women and their co-residing intimate partners and identifying the largest contribution to family income. The conceptual model was tested with structural equation modeling and showed acceptable fit. The prevalence of any type of intimate partner violence was 29.8% in São Luís and 20.1% in Ribeirão Preto. In both municipalities, pregnant women were more likely to suffer exclusive psychological and physical/sexual violence when they had the highest income in the family (p < 0.005). In São Luís, physical/sexual violence was more common among women who were better educated than their partners (standardized coefficient, SC = -0.466; p = 0.007). In Ribeirão Preto, exclusive psychological violence was more frequent among women who had lower status occupations than their partners (SC = 0.236; p = 0.004). Inversion of traditional gender roles is associated with exclusive psychological and physical/sexual violence against pregnant women by their co-residing intimate partners. These findings suggest that women's empowerment at an individual level does not necessarily relieve them of intimate partner abuse in social contexts where traditional gender norms persist.